2017
DOI: 10.1248/cpb.c17-00261
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Activity of an Antimetabolite Drug and Tyrosine Kinase Inhibitors against Breast Cancer Cells

Abstract: Antimetabolite drugs, including the adenosine deaminase inhibitor cladribine, have been shown to induce apoptosis in a variety of cancer cells, and have been widely used in clinical trials of various cancers in conjunction with tyrosine kinase inhibitors (TKIs). Combination treatment with cladribine and gefitinib or dasatinib is expected to have a synergistic inhibitory effect on breast cancer cell growth. Our results demonstrated that the combination treatment had synergistic activity against human breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Cladribine activates the intrinsic pathway of apoptosis by inducing caspases such as caspase −3, 7, −8, or −9. A decrease in the mitochondrial membrane potential leads to changes in the intracellular levels of calcium 9,33 . The present study clearly showed that the new derivatives significantly increased the levels of calcium ions to a greater extent than CLA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cladribine activates the intrinsic pathway of apoptosis by inducing caspases such as caspase −3, 7, −8, or −9. A decrease in the mitochondrial membrane potential leads to changes in the intracellular levels of calcium 9,33 . The present study clearly showed that the new derivatives significantly increased the levels of calcium ions to a greater extent than CLA.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism underlying the effect of cladribine is the induction of cell cycle arrest and condensation of chromosomes. Cladribine leads to the accumulation of cells in the G2/M phase at the expense of the G1 phase 9 . In HL-60 cells, the CLA-FMOR derivative increased the number of cells in the sub-G1 phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sal has been shown to induce iROS production, suppress the phosphoinositide 3-kinase/protein kinase B/mammalian target of rapamycin signaling pathways (PI3K/AKT/mTOR), and cause apoptosis in prostate, brain, and breast cancer cells [ 42 – 44 ]. Das can also induce iROS [ 45 ]. These provided the rationale for us to investigate whether the drug combination would enhance the ROS increase in different human BC cell lines including MDA-MB-468, MDA-MB-231, and MCF-7, and thereby promote cytotoxicity compared to using Sal or Das alone.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the synergistic activities of dasatinib + vorinostat, cladribine+dasatinib and cladribine+gefitinib were analyzed in detail. The results of the analysis showed that these three combinatorial drugs exert synergistic anti-cancer effects on MCF-7 cells by inducing cell cycle arrest, reactive oxygen (ROS) production and apoptosis through mitochondrial-mediated endogenous pathways [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%